Burundi 1972/Rwanda 1994 : the dramatic "efficiency" of an ideological rebuilding of the past by the press - (:unkn) unknown (My University, 2004)
The descriptions of the History of Rwanda and Burundi, made in colonial times, have thoroughly influenced the evolution of these two countries after their independence. The historical and spread version of a century old conflict between the Hutu and the Tutsi, reappropriated by the local elites and converted into the main tendencies of their political struggle, reappeared in a paroxystic way at the time of the two genocides in 1972 in Burundi, and in 1994 in Rwanda. The main Belgian and French daily papers hardly mentioned the first genocide in the region of the Great Lakes: in 1972 they contented themselves by using once more the commonplace ideas about tribal struggles as an analysis. Twenty years later, a special way in collecting informations out of the press is still being applied to African conflicts. Moreover, the acknowledgement of the genocide of the Rwandan tutsi didn't prevent the French and Belgian papers from using a “national” way of dealing with the information.
Keywords: African Research